Radiation of the flat plasma layer with small bending - Kirichenko, Y. V.; Karlov, V. D.; Kiyko, A. S. (Radiofizika i èlektronika, 2017)
Plasma antennas are the subject of intense theoretical and experimental studies. One of the types of plasma antennas is the so-called loop antenna, which is a curved gas discharge tube filled with cold plasma. An angle and curvature radius of the tube significantly affect radiation pattern and intensity of this antenna. In this paper, we theoretically study the model of the plasma loop antenna, which is a flat layer of plasma on a metal substrate with a small bending angle. Radiation patterns and energy transformation coefficients of the surface wave have been calculated for various parameters of the problem. It has been shown that up to 10% of the surface wave energy is converted into radiation at a bending angle of 0.3 rad. Radiation patterns have one petal with a maximum at acute angles.